The Role of Social Cognition Abilities in Parkinson's Disease in the Era of COVID-19 Emergency - Dodich, Alessandra; Papagno, Costanza; Turella, Luca; Meli, Claudia; Zappini, Francesca; Narduzzi, Pamela; Gober, Alessandro; Pierotti, Enrica; Falla, Marika (Frontiers in Psychology, 2021)
Introduction: Parkinson’s Disease (PD) is characterized by motor and non-motor symptoms, among which deficits in social cognition might affect approximately 20% of patients. This study aims to evaluate the role of social cognitive abilities in the perceived impact of COVID-19 emergency, and the effects of lockdown measures on patients’ social network and caregivers’ burden. Methods: Fourteen PD patients performed a neuropsychological battery including socio-cognitive tasks before the introduction of COVID-19 restrictive measures (i.e., social distancing and isolation). A structured interview through an online platform was performed in the last two weeks of the first lockdown phase to assess patient’s health status, perception of COVID-19 emergency and changes in caregiver’s burden and patients’ social isolation. Non-parametric analyses were performed to evaluate the association between social skills and patients’ COVID-19 perception, as well as the effects of restrictive measures. Results: At baseline evaluation half of PD patients showed socio-cognitive dysfunctions, mainly on mentalizing abilities. Patients with impaired social cognition skills showed a significant lower concern on the possible effects of COVID-19 on their health. Caregiver burden and patients’ social network remained stable during the lockdown. Conclusion: These preliminary results underline that PD socio-cognitive dysfunctions might affect patients’ ability to estimate the effects of COVID-19 infection. However, the lack of a significant increase in caregivers’ burden and social isolation suggests, in our sample, a good coping to COVID-19 emergency. Since COVID-19 pandemic can have direct and indirect severe consequences in patients with PD, the development of educational and preventive programs is recommended.